The Effect of Recruitment, Training, and Motivation on Employee Performance at CV. Bakti Pratama Charcoal Briquette Industry - Anis Oktavia (MANAJEMEN, 2026)
This research aims to analyze the effect of recruitment, training, and motivation on employee performance, both partially and simultaneously, at CV. Bakti Pratama Charcoal Briquette Industry, a small and medium-scale enterprise in the charcoal briquette industry in Ungaran City, Central Java. The background of the research is the increase in the number of employees leaving the company and the decline in employee productivity in recent years. The research employed a quantitative approach with a census sampling technique, selecting all 45 employees as respondents. Data were collected using a questionnaire with a 5-point Likert scale, which was validated for reliability and validity. Data analysis was conducted using multiple linear regression analysis. The results revealed that simultaneously, recruitment, training, and motivation have a positive and significant effect on employee performance, contributing 78.6%. Partially, training and motivation have a positive and significant effect on employee performance. Motivation was found to be the most dominant factor influencing employee performance. On the other hand, recruitment had no significant partial effect. This proves that although recruitment provides a foundation for a company, long-term employee performance depends more on investment in training and motivation.